Identification of Abscisic Acid-Dependent Phosphorylated Basic Helix-Loop-Helix Transcription Factors in Guard Cells of Vicia faba by Mass Spectrometry - Hayashi, Yuki; Takahashi, Yohei; Fukatsu, Kohei; Tada, Yasuomi; Takahashi, Koji; Kuwata, Keiko; Suzuki, Takamasa; Kinoshita, Toshinori (Frontiers in Plant Science, 2021)
An unknown 61 kDa protein is phosphorylated by abscisic acid (ABA)-activated protein kinase in response to ABA and binds to 14-3-3 protein in a phosphorylation-dependent manner in guard cell protoplasts (GCPs) from Vicia faba. Subsequently, ABA-dependent phosphorylated proteins were identified as basic helix-loop-helix transcription factors, named ABA-responsive kinase substrates (AKSs) in GCPs from Arabidopsis thaliana. However, whether the 61 kDa protein in Vicia GCPs is an AKS is unclear. We performed immunoprecipitation of ABA-treated Vicia GCPs using anti-14-3-3 protein antibodies and identified several AKS isoforms in V. faba (VfAKSs) by mass spectrometry. The 61 kDa protein was identified as VfAKS1. Phosphoproteomic analysis revealed that VfAKSs are phosphorylated at Ser residues, which are important for 14-3-3 protein binding and monomerisation, in response to ABA in GCPs. Orthologs of AtABCG40, an ABA importer in guard cells, and CHC1, a clathrin heavy chain and a regulator of stomatal movement, also co-immunoprecipitated with 14-3-3 protein from guard cells.